The Development Process, Current Status, and Prospects of Population Geography in China - Yang, Zhiying; Su, Zhen; Wang, Wanru (International Journal of Social Sciences and Public Administration, 2025)
Human geography in China has a long history, but its substantial development began after the founding of the People’s Republic of China and accelerated significantly following the Reform and Opening-Up. Population geography, as an interdisciplinary field integrating demography, geography, sociology, and quantitative methods, has evolved to address national population policies and emerging challenges. Modern research focuses on population distribution, migration, urbanization, and contemporary issues such as aging populations, counter-urbanization, declining birth rates, and the impact of the COVID-19 pandemic. These studies aim to optimize China’s population structure and spatial patterns. With the gradual disappearance of the demographic dividend and increasing regional disparities, population geography has become a critical discipline for guiding sustainable development. This paper reviews the historical trajectory, key research themes, and future directions of population geography in China, highlighting its role in addressing complex socio-demographic challenges and informing policy-making.